CALCULATION OF BUILDINGS WITH COMPLEX GEOMETRIC SHAPES FOR WITHSTANDING WIND IMPACT - E. K. Agakhanov; G. M. Kravchenko; A. S. Osadchiy; E. V. Trufanova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The possibility of modeling wind flow during the design of buildings with complex geometric shapes in order to determine comfort parameters and zones is considered.Methods. The investigation of the impact of wind on a cylindrical building was carried out using Ansys 15.0 software.Results. A finite element model of a modern art museum building having a complex geometric shape is developed for the calculation of the wind flow and the definition of comfort zones. The computational region is chosen such that its borders do not affect the calculation results. The maximum wind speed is assumed to be 44 m/s at an altitude of 10 m from the ground level, this being the maximum in the region of Novorossiysk. The topography of the earth's surface around the model was considered flat. The surface of the building was assumed to be smooth while the surface of the surrounding terrain was assumed to be rough with a roughness parameter of 0,1 m. The parameters of the building orientation relative to the wind rise were varied during the numerical modeling. Three variants of computational models with varying building location and its geometric characteristics are developed. In the first variant, the building model is stretched along the X-axis; in the second variant, the acute angle of the building model's contour is oriented along the Y-axis; in the third variant, the building model is located and oriented along the Y-axis with its obtuse angle of the external contour of the building. The calculation results of a cylindrical building for wind impact correspond to SP 20.13330.2011. The comfort parameters and zones of a building having complex geometric shape are defined by means of numerical modeling of the wind flow. The discrepancy between the object's normative characteristics and the research results is revealed during the calculation of the wind load.Conclusion. The recommendations are given for choosing the optimal location of the museum building, taking into account the comfort parameters and the greatest wind pressure; the geometric shape of the outer contour affects the location of the zones of reduced comfort; a sharp change in the boundaries of the outer contour leads to the appearance of increased pressure and wind speed and, as a consequence, a change in the direction of the vortex flows; it is necessary to apply the finite element method when modeling the wind impact for buildings of complex geometric shapes; sudden changes in the object's contour should be avoided when designing buildings and structures.